Synthesis and Characterization of Catalytically Active Au Core─Pd Shell Nanoparticles Supported on Alumina - Feng, Yanyue; Schaefer, Andreas; Hellman, Anders; Di, Mengqiao; Härelind, Hanna; Bauer, Matthias; Carlsson, Per-Anders (Langmuir)
A two-step seeded-growth method was refined to synthesize Au@Pd core@shell nanoparticles with thin Pd shells, which were then deposited onto alumina to obtain a supported Au@Pd/Al2O3 catalyst active for prototypical CO oxidation. By the strict control of temperature and Pd/Au molar ratio and the use of l-ascorbic acid for making both Au cores and Pd shells, a 1.5 nm Pd layer is formed around the Au core, as evidenced by transmission electron microscopy and energy-dispersive spectroscopy. The core@shell structure and the Pd shell remain intact upon deposition onto alumina and after being used for CO oxidation, as revealed by additional X-ray diffraction and X-ray photoemission spectroscopy before and after the reaction. The Pd shell surface was characterized with in situ infrared (IR) spectroscopy using CO as a chemical probe during CO adsorption–desorption. The IR bands for CO ad-species on the Pd shell suggest that the shell exposes mostly low-index surfaces, likely Pd(111) as the majority facet. Generally, the IR bands are blue-shifted as compared to conventional Pd/alumina catalysts, which may be due to the different support materials for Pd, Au versus Al2O3, and/or less strain of the Pd shell. Frequencies obtained from density functional calculations suggest the latter to be significant. Further, the catalytic CO oxidation ignition-extinction processes were followed by in situ IR, which shows the common CO poisoning and kinetic behavior associated with competitive adsorption of CO and O2 that is typically observed for noble metal catalysts.
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Single-Layer T′ Nickelates: Synthesis of the La and Pr Members and Electronic Properties across the Rare-Earth Series - Wissel, Kerstin; Bernardini, Fabio; Oh, Heesu; Vasala, Sami; Schoch, Roland; Blaschkowski, Björn; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver; Cano, Andrés (Chemistry of Materials)
Understanding high-temperature unconventional superconductivity has become a long-lasting problem in which the cuprates stand as central reference materials. Given this impasse, the recent discovery of superconductivity in analogous nickelate thin films represents a fundamental breakthrough calling for the identification of additional materials in this class. In particular, thermodynamically more robust systems are required to “upgrade” nickelate superconductors from thin films to bulk samples. Here, we contribute in this direction by reporting the synthesis of the new single-layer T′ Pr2NiO3F compound, assessing this synthesis in relation to the only previous T′ nickelate La2NiO3F, and analyzing the electronic properties across the R2NiO3F series (R = La–Lu) via first-principles calculations. We find that these mixed anion systems have a comparatively high degree of stability and their synthesis enables a fine-tuning of their composition as inferred from their characterization. Furthermore, we find that these unprecedented square-planar nickelates hold great promise as prospective superconductors due to their exceptional electronic structure.
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Pseudo‐Octahedral Iron(II) Complexes with Near‐Degenerate Charge Transfer and Ligand Field States at the Franck‐Condon Geometry - Moll, Johannes; Naumann, Robert; Sorge, Lukas; Förster, Christoph; Gessner, Niklas; Burkhardt, Lukas; Ugur, Naz; Nuernberger, Patrick; Seidel, Wolfram; Ramanan, Charusheela; Bauer, Matthias; Heinze, Katja (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Quality or Quantity? How Structural Parameters Affect Catalytic Activity of Iron Oxides for CO Oxidation - Schlicher, Steffen; Prinz, Nils; Bürger, Julius; Omlor, Andreas; Singer, Christian; Zobel, Mirijam; Schoch, Roland; Lindner, Jörg K. N.; Schünemann, Volker; Kureti, Sven; Bauer, Matthias (Catalysts)
<The replacement of noble metal catalysts by abundant iron as an active compound in CO oxidation is of ecologic and economic interest. However, improvement of their catalytic performance to the same level as state-of-the-art noble metal catalysts requires an in depth understanding of their working principle on an atomic level. As a contribution to this aim, a series of iron oxide catalysts with varying Fe loadings from 1 to 20 wt% immobilized on a γ-Al2O3 support is presented here, and a multidimensional structure–activity correlation is established. The CO oxidation activity is correlated to structural details obtained by various spectroscopic, diffraction, and microscopic methods, such as PXRD, PDF analysis, DRUVS, Mössbauer spectroscopy, STEM-EDX, and XAS. Low Fe loadings lead to less agglomerated but high percentual amounts of isolated, tetrahedrally coordinated iron oxide species, while the absolute amount of isolated species reaches its maximum at high Fe loadings. Consequently, the highest CO oxidation activity in terms of turnover frequencies can be correlated to small, finely dispersed iron oxide species with a large amount of tetrahedrally oxygen coordinated iron sites, while the overall amount of isolated iron oxide species correlates with a lower light-off temperature.
Keywords: Physical and Theoretical Chemistry; Catalysis; General Environmental Science; Key

High resolution off resonant spectroscopy as a probe of the oxidation state - Nowakowski, Michał; Kalinko, Aleksandr; Szlachetko, Jakub; Fanselow, Rafał; Bauer, Matthias (Journal of Analytical Atomic Spectrometry)
Currently, chemistry and physics are strongly dependent on the concept of the oxidation state. While the formal oxidation state is easily evaluated, the real physical oxidation state value is often difficult to determine and significantly varies from the formal values. Determination of the ionization threshold in X-ray absorption spectroscopy (XANES) relies on the absorption edge position and sometimes poses limitations, mainly due to the edge resonances. Moreover, the lower energy states can be probed only within x-soft or XUV photons providing only surface state information of probed materials. Here, we employ high energy resolution off-resonant spectroscopy to determine both 1s and 3p binding energies of Fe-based materials and therefore correlate to their physical oxidation state. The results are compared to the ones obtained with classical X-ray absorption, X-ray emission, and photoelectron spectroscopies. The observed differences in binding energies are discussed in a frame of initial and final state interactions with the atom's electronic configurations. The presented methodology is discussed towards potential use to single-shot experiments and application at X-ray free-electron lasers. Alternatively, core level X-ray emission spectroscopy can be used, but the emission line positions are strongly affected by spin-orbit interaction. However, due to the energy transfer from the photon to the excited core electron, the same information as in XANES is probed in high energy resolution off-resonant spectroscopy (HEROS). Based on the Kramers–Heisenberg theory, we propose a new approach for ionization threshold determination which is free of the limitations encountered in XANES-based determination of the core state energy. Namely, the value of core state energy can be determined analytically using a few HEROS spectra recorded with significantly higher spectral resolution. This approach provides a basis for the universal physical oxidation state determination method.
Keywords: Spectroscopy; Analytical Chemistry

Digitization in Catalysis Research: Towards a Holistic Description of a Ni/Al2O3 Reference Catalyst for CO2 Methanation - Weber, Sebastian; Zimmermann, Ronny T.; Bremer, Jens; Abel, Ken L.; Poppitz, David; Prinz, Nils; Ilsemann, Jan; Wendholt, Sven; Yang, Qingxin; Pashminehazar, Reihaneh; Monaco, Federico; Cloetens, Peter; et al. (ChemCatChem)
Increasing the metal-to-ligand charge transfer (MLCT) excited state lifetime of polypyridine iron(II) complexes can be achieved by lowering the ligand's π* orbital energy and by increasing the ligand field splitting. In the homo- and heteroleptic complexes [Fe(cpmp)2]2+ (12+) and [Fe(cpmp)(ddpd)]2+ (22+) with the tridentate ligands 6,2’’-carboxypyridyl-2,2’-methylamine-pyridyl-pyridine (cpmp) and N,N’-dimethyl-N,N’-di-pyridin-2-ylpyridine-2,6-diamine (ddpd) two or one dipyridyl ketone moieties provide low energy π* acceptor orbitals. A good metal-ligand orbital overlap to increase the ligand field splitting is achieved by optimizing the octahedricity through CO and NMe units between the coordinating pyridines which enable the formation of six-membered chelate rings. The push-pull ligand cpmp provides intra-ligand and ligand-to-ligand charge transfer (ILCT, LL'CT) excited states in addition to MLCT excited states. Ground and excited state properties of 12+ and 22+ were accessed by X-ray diffraction analyses, resonance Raman spectroscopy, (spectro)electrochemistry, EPR spectroscopy, X-ray emission spectroscopy, static and time-resolved IR and UV/Vis/NIR absorption spectroscopy as well as quantum chemical calculations.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Understanding the Redox Mechanism of Sulfurized Poly(acrylonitrile) as Highly Rate and Cycle Stable Cathode Material for Sodium-Sulfur Batteries - Kappler, Julian; Tonbul, Güldeniz; Schoch, Roland; Murugan, Saravanakumar; Nowakowski, Michał; Lange, Pia Lena; Klostermann, Sina Vanessa; Bauer, Matthias; Schleid, Thomas; Kästner, Johannes; Buchmeiser, Michael Rudolf (Journal of The Electrochemical Society)
Room temperature sodium-sulfur (RT Na-S) batteries are considered potential candidates for stationary power storage applications due to their low cost, broad active material availability and low toxicity. Challenges, such as high volume expansion of the S-cathode upon discharge, low electronic conductivity of S as active material and herewith limited rate capability as well as the shuttling of polysulfides (PSs) as intermediates often impede the cycle stability and practical application of Na-S batteries. Sulfurized poly(acrylonitrile) (SPAN) inherently inhibits the shuttling of PSs and shows compatibility with carbonate-based electrolytes, however, its exact redox mechanism remained unclear to date. Herein, we implement a commercially available and simple electrolyte into the Na-SPAN cell chemistry and demonstrate its high rate and cycle stability. Through the application of in situ techniques utilizing electronic impedance spectroscopy (EIS) and X-ray absorption spectroscopy (XAS) at different depths of charge and discharge, an insight into SPAN’s redox chemistry is obtained.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Structural transitions during Ni nanoparticle formation by decomposition of a Ni-containing metal-organic framework using in-situ total scattering - Prinz, Nils; Strübbe, Sven; Bauer, Matthias; Zobel, Mirijam (New Journal of Chemistry)
For improved and rational design of catalysts, in-depth knowledge of their formation and structural evolution during synthesis is a key parameter. Thus, preparation of a Ni methanation catalyst derived from...
Keywords: Materials Chemistry; General Chemistry; Catalysis

Ultrafast two-colour X-ray emission spectroscopy reveals excited state landscape in a base metal dyad - Bauer, Matthias (Ultrafast two-colour X-ray emission spectroscopy reveals excited state landscape in a base metal dyad)

Iron(III)-Complexes with N-Phenylpyrazole-Based Ligands - Hirschhausen, Tanja; Fritsch, Lorena; Lux, Franziska; Steube, Jakob; Schoch, Roland; Neuba, Adam; Egold, Hans; Bauer, Matthias (Inorganics)
The use of iron as a replacement for noble metals in photochemical and photophysical applications is challenging due to the typically fast deactivation of short-lived catalytically active states. Recent success of a cyclometalated iron(III) complex utilizing a bis-tridentate ligand motif inspired the use of phenyl-1H-pyrazole as a bidentate ligand. Five complexes using the tris(1-phenylpyrazolato-N,C2)iron(III) complex scaffold are presented. In addition to the parent complex, four derivatives with functionalization in the meta-position of the phenyl ring are thoroughly investigated by single crystal diffractometry, UV-Vis-spectroscopy, and cyclic voltammetry. Advanced X-ray spectroscopy in the form of X-ray absorption and emission spectroscopy allows unique insights into the electronic structure as well as DFT calculations. The ligand design leads to overlapping MLCT and LMCT absorption bands, and emissive behavior is suppressed by low-lying MC states.
Keywords: Inorganic Chemistry; Computing Resources Provided by the Paderborn Center for Parallel Computing; pc2-ressources

Direct Synthesis of Acetone by Aerobic Propane Oxidation Promoted by Photoactive Iron(III) Chloride under Mild Conditions - Rogolino, Andrea; Filho, José B. G.; Fritsch, Lorena; Ardisson, José D.; da Silva, Marcos A. R.; Atta Diab, Gabriel Ali; Silva, Ingrid Fernandes; Moraes, Carlos André Ferreira; Forim, Moacir Rossi; Bauer, Matthias; Kühne, Thomas D.; Antonietti, Markus; et al. (ACS Catalysis)
Keywords: Catalysis; General Chemistry; pc2-ressources; Computing Resources Provided by the Paderborn Center for Parallel Computing

Electronic Structure and Excited-State Dynamics of the NIR-II Emissive Molybdenum(III) Analogue to the Molecular Ruby - Kitzmann, Winald R.; Hunger, David; Reponen, Antti-Pekka M.; Förster, Christoph; Schoch, Roland; Bauer, Matthias; Feldmann, Sascha; van Slageren, Joris; Heinze, Katja (Inorganic Chemistry)
Photoactive chromium(III) complexes saw a conceptual breakthrough with the discovery of the prototypical molecular ruby mer-[Cr(ddpd)2]3+ (ddpd = N,N′-dimethyl-N,N′-dipyridin-2-ylpyridine-2,6-diamine), which shows intense long-lived near-infrared (NIR) phosphorescence from metal-centered spin-flip states. In contrast to the numerous studies on chromium(III) photophysics, only 10 luminescent molybdenum(III) complexes have been reported so far. Here, we present the synthesis and characterization of mer-MoX3(ddpd) (1, X = Cl; 2, X = Br) and cisfac-[Mo(ddpd)2]3+ (cisfac-[3]3+), an isomeric heavy homologue of the prototypical molecular ruby. For cisfac-[3]3+, we found strong zero-field splitting using magnetic susceptibility measurements and electron paramagnetic resonance spectroscopy. Electronic spectra covering the spin-forbidden transitions show that the spin-flip states in mer-1, mer-2, and cisfac-[3]3+ are much lower in energy than those in comparable chromium(III) compounds. While all three complexes show weak spin-flip phosphorescence in NIR-II, the emission of cisfac-[3]3+ peaking at 1550 nm is particularly low in energy. Femtosecond transient absorption spectroscopy reveals a short excited-state lifetime of 1.4 ns, 6 orders of magnitude shorter than that of mer-[Cr(ddpd)2]3+. Using density functional theory and ab initio multireference calculations, we break down the reasons for this disparity and derive principles for the design of future stable photoactive molybdenum(III) complexes.
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Chemical and photophysical properties of amine functionalized bis‐NHC‐pyridine‐RuII complexes - Fritsch, Lorena; Vukadinovic, Yannik; Lang, Moritz; Naumann, Robert; Bertrams, Maria-Sophie; Kruse, Ayla; Schoch, Roland; Müller, Patrick; Neuba, Adam; Dierks, Philipp; Lochbrunner, Stefan; Kerzig, Christoph; et al. (ChemPhotoChem)
The effects of backbone amine functionalization in three new homoleptic C^N^C type ruthenium(II) complexes bearing a tridentate bis‐imidazole‐2‐ylidene pyridine ligand framework are characterized and studied by single crystal diffraction, electrochemistry, optical spectroscopy and transient absorption spectroscopy in combination with ab initio DFT calculations. Functionalization by dimethylamine groups in 4‐position of the pyridine backbone significantly influences the properties of the complexes as revealed by comparison with the unfunctionalized references. As a result of the amine functionalization, a higher molar absorption coefficient of the MLCT bands, a decreased photoluminescence quantum yield at room temperature together with a shortened excited state lifetime but an improved photostability is observed. Introduction of electron donating and withdrawing groups at the NHC unit modifies the electronic and optical properties, such as the oxidation potential, absorption and emission properties, and the lifetimes of the excited states.
Keywords: Organic Chemistry; Physical and Theoretical Chemistry; Analytical Chemistry; Computing Resources Provided by the Paderborn Center for Parallel Computing; pc2-ressources

Macrocyclization of Dienes under Confinement with Cationic Tungsten Imido/Oxo Alkylidene N‐Heterocyclic Carbene Complexes - Ziegler, Felix; Bruckner, Johanna R.; Nowakowski, Michał; Bauer, Matthias; Probst, Patrick; Atwi, Boshra; Buchmeiser, Michael R. (ChemCatChem)
Macrocyclization reactions are still challenging due to competing oligomerization, which requires the use of small substrate concentrations. Here, the cationic tungsten imido and tungsten oxo alkylidene N-heterocyclic carbene complexes [[W(N-2,6-Cl2-C6H3)(CHCMe2Ph(OC6F5)(pivalonitrile)(IMes)+ B(ArF)4−] (W1) and [W(O)(CHCMe2Ph(OCMe(CF3)2)(IMes)(CH3CN)+ B(ArF)4−] (W2) (IMes=1,3-dimesitylimidazol-2-ylidene; B(ArF)4−=tetrakis(3,5-bis(trifluoromethyl)phenyl borate) have been immobilized inside the pores of ordered mesoporous silica (OMS) with pore diameters of 3.3 and 6.8 nm, respectively, using a pore-selective immobilization protocol. X-ray absorption spectroscopy of W1@OMS showed that even though the catalyst structure is contracted due to confinement by the mesopores, both the oxidation state and structure of the catalyst stayed intact upon immobilization. Catalytic testing with four differently sized α,ω-dienes revealed a dramatically increased macrocyclization (MC) and Z-selectivity of the supported catalysts compared to the homogenous progenitors, allowing high substrate concentrations of 25 mM. With the supported complexes, a maximum increase in MC-selectivity from 27 to 81 % and in Z-selectivity from 17 to 34 % was achieved. In general, smaller mesopores exhibited a stronger confinement effect. A comparison of the two supported tungsten-based catalysts showed that W1@OMS possesses a higher MC-selectivity, while W2@OMS exhibits a higher Z-selectivity which can be rationalized by the structures of the catalysts.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

High‐Resolution X‐ray Absorption and Emission Spectroscopy for Detailed Analysis of New CO2 Methanation Catalysts - Strübbe, Sven; Nowakowski, Michał; Schoch, Roland; Bauer, Matthias (ChemPhysChem)
Abstract A new approach for the characterization of CO 2 methanation catalysts prepared by thermal decomposition of a nickel MOF by hard X‐ray photon‐in/photon‐out spectroscopy in form of high energy resolution fluorescence detected X‐ray absorption near edge structure spectroscopy (HERFD‐XANES) and valence‐to‐core X‐ray emission (VtC‐XES) is presented. In contrast to conventional X‐ray absorption spectroscopy, the increased resolution of both methods allows a more precise phase determination of the final catalyst, which is influenced by the conditions during MOF decomposition.
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Insights into the First Multi-Transition-Metal Containing Ruddlesden Popper-Type Cathode for all-solid-state Fluoride Ion Batteries - Vanita, Vanita; Waidha, Aamir Iqbal; Vasala, Sami; Puphal, Pascal; Schoch, Roland; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver (Journal of Materials Chemistry A)
Promising cathode materials for fluoride-ion batteries (FIBs) are 3d transition metal containing oxides with Ruddlesden-Popper-type structure. So far, multi-elemental compositions were not investigated, but could alternate electrochemical performance similar to what has been found for cathode materials for lithium-ion batteries. Within this study, we investigate RP type La2Ni0.75Co0.25O4.08 as an intercalation-based active cathode material for all-solid-state FIBs. We determine the structural changes of La2Ni0.75Co0.25O4.08 during fluoride intercalation / de-intercalation by ex-situ X-ray diffraction, which showed that F- insertion leads to transformation of the parent phase to three different phases. Changes in Ni and Co oxidation states and coordination environment were examined by X-ray absorption spectroscopy and magnetic measurements in order to understand the complex reaction behaviour of the phases in detail, showing that the two transition metals behave differently in the charging and discharging process. Under optimized operating conditions, a cycle life of 120 cycles at a critical cut-off capacity of 40 mAh g-1 against Pb/PbF2 was obtained, which is one of the highest observed for intercalation electrode materials in FIBs so far. The average Coulombic efficiencies ranged from 85% to 90%. Thus, La2Ni0.75Co0.25O4.08 could be a promising candidate for cycling-stable high-energy cathode materials for all-solid-state FIBs
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Detection and Characterization of Hydride Ligands in Copper Complexes by Hard X‐ray Spectroscopy - Fritsch, Lorena; Rehsies, Pia; Barakat, Wael; Estes, Deven P.; Bauer, Matthias (Chemistry – A European Journal)
Transition metal complexes, particularly copper hydrides, play an important role in various catalytic processes and molecular inorganic chemistry. This study employs synchrotron hard X‐ray spectroscopy to gain insights into the geometric and electronic properties of copper hydrides as potential catalysts for CO2 hydrogenation. The potential of high energy resolution X‐ray absorption near‐edge structure (HERFD‐XANES) and valence‐to‐core X‐ray emission (VtC‐XES) is demonstrated with measurement on Stryker's reagent (Cu6H6) and [Cu3(μ3‐H)(dpmppe)2](PF6)2 (Cu3H), alongside a non‐hydride copper compound (Cu‐I). The XANES analysis reveals that coordination geometries strongly influence the spectra, providing only indirect details about hydride coordination. The VtC‐XES analysis exhibits a distinct signal around 8975 eV, offering a diagnostic tool to identify hydride ligands. Theoretical calculations support and extend these findings by comparing hydride‐containing complexes with their hydride‐free counterparts.